Seismic Response of Liquid Storage Ground Supported Tanks for Different Slenderness Ratio - Kotrasová Kamila (Transactions of the VŠB: Technical University of Ostrava, Civil Engineering Series, 2016)
Ground-supported cylindrical tanks are used to store a variety of liquids. This paper provides the theoretical background for takes into account impulsive and convective (sloshing) actions of the fluid in concrete containers fixed to rigid foundations; it has been adopted in Eurocode 8. Seismic responses - base shears, the bending and overturning moments - are calculated by using the response spectra of the earthquake in Loma Prieta, California (18.10.1989). As the examples is analyzed the ground supported cylindrical concrete tanks, fluid filling is H = 2 m and R are depended from tank slenderness ratio γ = H/R. For considered tank slenderness ratios γ = 0.3, 0.5, 0.7, 1, 2, 3 R are given 6.667 m, 4 m, 2.857 m, 2 m, 1 m and 0.667 m.